2014
DOI: 10.1007/s10549-014-3089-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of H3K9me3 and H3K27me3 repressive histone marks with breast cancer subtypes in the Nurses’ Health Study

Abstract: Repressive histone tail modifications have been associated with molecular breast cancer subtypes. We investigated whether histone 3 lysine 9 trimethylation (H3K9me3) and histone 3 lysine 27 trimethylation (H3K27me3) were associated with tumor features and subtypes while adjusting for prospectively collected reproductive and lifestyle breast cancer risk factors. We have tissue microarray data with immunohistochemical marker information on 804 incident cases of invasive breast cancer diagnosed from 1976-2000 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 41 publications
8
30
0
Order By: Relevance
“…Thus, PRC2 activity might not be sufficient to maintain the mark in rapidly dividing breast cancer cells. We propose that these observations reconcile contradictory data reporting inverse variations of EZH2 and H3K27me3 in several tumor types (Wei et al 2008;Holm et al 2012;Xu et al 2012;Healey et al 2014;Bae et al 2015).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Thus, PRC2 activity might not be sufficient to maintain the mark in rapidly dividing breast cancer cells. We propose that these observations reconcile contradictory data reporting inverse variations of EZH2 and H3K27me3 in several tumor types (Wei et al 2008;Holm et al 2012;Xu et al 2012;Healey et al 2014;Bae et al 2015).…”
Section: Discussionsupporting
confidence: 84%
“…Paradoxically, recent studies have reported that the levels of H3K27me3 are decreased in several solid tumor types, including breast and prostate (Wei et al 2008;Holm et al 2012;Xu et al 2012;Healey et al 2014;Bae et al 2015). Even more surprising, the levels of the enzyme and the mark were found to be anti-correlated between the different breast cancer subtypes (Holm et al 2012), and, while high expression of EZH2 correlates with poor prognosis, high levels of H3K27me3 correlate with good prognosis (Holm et al 2012;Bae et al 2015).…”
mentioning
confidence: 99%
“…There was an inverse correlation between H3K27me3 and EZH2 expression in different tumor types and tumor grades as high expression of EZH2 was associated with high grades and ER(−)/PR(−) tumors and these tumors were observed to have low H3K27me3 levels [ 75 ]. Consistent with this study, examination of H3K27me3 on tissue micro arrays in the Nurses' Health Study demonstrated a signifi cant association of H3K27me3 mark with lower tumor grade and a positive association with ER(+) and PR(+) tumors [ 68 ]. Finally, H3K27me3 was also observed to be positively associated with luminal subtype A breast cancers [ 68 , 75 ].…”
Section: Global Histone Modifi Cationssupporting
confidence: 82%
“…Moreover, high-grade breast, ovarian, and pancreatic cancers have been found to harbor low global H3K27me3, which is correlated with increased recurrence and poor survival (19)(20)(21). Particularly in breast cancer, EZH2 and H3K27me3 levels are found to be not correlated across different subtypes, with higher expression of EZH2 in basal-like/TNBC and HER2 + tumors, and high H3K27me3 level in luminal A, luminal B, and normal-like tumors (19,22). Consequently, a high EZH2 expression is associated with poor disease outcome (19,20,23), and a high H3K27me3 level is associated with better outcome (19,20,22).…”
mentioning
confidence: 99%
“…Particularly in breast cancer, EZH2 and H3K27me3 levels are found to be not correlated across different subtypes, with higher expression of EZH2 in basal-like/TNBC and HER2 + tumors, and high H3K27me3 level in luminal A, luminal B, and normal-like tumors (19,22). Consequently, a high EZH2 expression is associated with poor disease outcome (19,20,23), and a high H3K27me3 level is associated with better outcome (19,20,22). Thus, the oncogenic function of Ezh2 in TNBC is not well coupled with the H3K27me3 level; instead, it might be more connected to its nonepigenetic silencing effect.…”
mentioning
confidence: 99%